2023
DOI: 10.1213/ane.0000000000006487
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine Pretreatment Protects Against Myocardial Ischemia/Reperfusion Injury by Activating STAT3 Signaling

Abstract: BACKGROUND: Myocardial infarction is a common perioperative complication, and blood flow restoration causes ischemia/reperfusion injury (IRI). Dexmedetomidine (DEX) pretreatment can protect against cardiac IRI, but the mechanism is still insufficiently understood. METHODS: In vivo, myocardial ischemia/reperfusion (30 minutes/120 minutes) was induced via ligation and then reperfusion of the left anterior descending coronary artery (LAD) in mice. Intraven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…It has been previously suggested that DEX may have myocardial protective effects in patients undergoing cardiac surgery and reduce postoperative cardiac mortality and the incidence of myocardial infarction in high-risk patients undergoing non-cardiac surgery [ 3 , 5 ]. Lab studies have demonstrated a reduction of myocardial inflammation, oxidative stress, and cellular apoptosis, though the exact mechanism is unknown [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously suggested that DEX may have myocardial protective effects in patients undergoing cardiac surgery and reduce postoperative cardiac mortality and the incidence of myocardial infarction in high-risk patients undergoing non-cardiac surgery [ 3 , 5 ]. Lab studies have demonstrated a reduction of myocardial inflammation, oxidative stress, and cellular apoptosis, though the exact mechanism is unknown [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, also other compounds have been described that activate STAT3 and are causally involved in cardioprotection under experimental conditions. The anabolic steroid nandrolone decanoate [ 22 ] and dexmedetomidine—a selective alpha 2 adrenoceptor agonist [ 19 ] reduced infarct size/biomarker release reflecting myocardial injury in rodents via STAT3 activation. Again, improved mitochondrial function was also associated with cardioprotection.…”
Section: Cardioprotective Effects Of Sglt2 Inhibitors Through Stat3 A...mentioning
confidence: 99%